AB0335 Assessment of Adrenal Reserve in Patients with Rheumatoid Arthritis. (9th June 2015) - Singh, B.K.; Jain, V.K.; Kamalnathan, S.K.; Negi, V.S.
Abstract : Background: The hypothalamic-pituitary-adrenal (HPA) axis plays an important role in regulating immune responses. Deficiency in HPA function might contribute to pathogenesis and persistence of rheumatoid arthritis (RA) (1, 2). Previous steroid use may also be an important cause for HPA insufficiency as abrupt withdrawal may lead to precipitation of adrenal insufficiency. Therefore, there is a need to assess the functional status of HPA axis to aid the management of patients. Objectives: To assess adrenal functions (reserve) in patients with rheumatoid arthritis and to identify the factors associated with it. Methods: Low dose ACTH (1μg) stimulation test was performed for 137 RA patients and blood samples were collected after 30 minutes for cortisol response. Serum cortisol of >18 μg/ml was considered as normal response (3). Presence of adrenal insufficiency was analyzed for possible association with age of onset, sex, duration, previous steroid use, RF, Anti-cyclic citrullinated peptide antibodies (ACPA), VAS, HAQ-Indian and DAS28 using SPSS v.17 software (IBM, India). Results: Thirty one (22.7%) patients were found to have adrenal insufficiency. Patients with adrenal insufficiency had significantly higher (p<0.05) DAS 28 & ACPA titers. On logistic regression ESR and tender Joint count (TJ) were found to be significantly associated with adrenal insufficiency. However, there was no association was found for sex group, age of onset, duration, auto-antibody profile, extra-articular manifestations, hsCRP, DAS 28, treatment with DMARD's and previous steroid use (>3 month back). Conclusions: Significant number of patients with rheumatoid arthritis had adrenal insufficiency, which was higher in patients with active disease. It emphasizes the concept of relative adrenal insufficiency in RA (4, 5). and necessitates further evaluation in a larger cohort to find other associations like inflammatory cytokines or genetics and to explore the cause or effect relationship between RA and adrenal insufficiency. References: Cutolo M, Foppiani L, Minuto F. Hypothalamic-pituitary-adrenal axis impairment in the pathogenesis of rheumatoid arthritis and polymyalgia rheumatica. J Endocrinol Invest. 2002;25(10 Suppl):19–23. Straub RH, Paimela L, Peltomaa R, Schölmerich J, Leirisalo-Repo M. Inadequately low serum levels of steroid hormones in relation to interleukin-6 and tumor necrosis factor in untreated patients with early rheumatoid arthritis and reactive arthritis. Arthritis Rheum. 2002 Mar;46(3):654–62. Crowley S, Hindmarsh PC, Holownia P, Honour JW, Brook CG. The use of low doses of ACTH in the investigation of adrenal function in man. J Endocrinol. 1991 Sep;130(3):475–9. Masi AT, Aldag JC, Jacobs JWG. Rheumatoid arthritis: neuroendocrine immune integrated physiopathogenetic perspectives and therapy. Rheum Dis Clin North Am. 2005 Feb;31(1):131–60, x. Gudbjörnsson B, Skogseid B, Oberg K, Wide L, Hällgren R. Intact adrenocorticotropic hormone secretion but impaired cortisol response in patients with active rheumatoid arthritis. Effect of glucocorticoids. J Rheumatol. 1996 Apr;23(4):596–602. Disclosure of Interest: None declared